Permanent His bundle pacing using a new tridimensional delivery sheath and a standard active fixation pacing lead: The telescopic technique. (19th January 2021) - Zingarini, Gianluca; Notaristefano, Francesco; Spighi, Lorenzo; Bagliani, Giuseppe; Cavallini, Claudio
Abstract: Introduction: Permanent His bundle pacing (PHBP) preserves physiological ventricular activation but technical difficulties have limited its widespread use. We report the first experience of PHBP performed with a new specific delivery sheath (Selectra 3D, Biotronik, Berlin, Germany) and an extendable‐retractable active screw, stylet‐driven pacing lead (Solia S 60, Biotronik). Methods and Results: Clinical, procedural, ECG, and electrical data from consecutive patients undergoing PHBP with this system were collected at implantation, and follow‐up was performed after 1 month. Our cohort included 17 patients (71% males; mean age 76 ± 8 years) undergoing permanent pacing for sick sinus syndrome (59%) or atrioventricular block (41%). PHBP was successful in 15 (88%) procedures with mean procedure and fluoroscopy times of 63 ± 14 and 13 ± 5 min, respectively. The pacing threshold was 2.1 ± 1.1 V @1 ms and the sensed R‐wave amplitude was 5.6 ± 3.5 mV; bipolar and unipolar pacing impedances were 526 ± 115 and 369 ± 109 Ω, respectively. At discharge, neither procedure‐related complications nor lead dislodgement or pacing capture failures was reported. After 1 month, 14 (93%) patients still demonstrated His bundle stimulation and one (7%) lost His bundle capture but the lead revision was not necessary because the myocardial pacing threshold was stable. Follow‐up threshold (2 ± 1.1 vs. 2.3 ± 1.2 V@1 ms, p = .239) and sensed R‐wave amplitude (5.6 ± 3.4 vs. 6.4 ± 2.5, p = .403) was unchanged compared to the acute phase. Conclusion: PHBP performed with a standard active fixation pacing lead and a new delivery sheath for His pacing is feasible, safe and demonstrates clinically acceptable electric performance both at implantation and after 1 month.